Bacterial 16S rRNA gene alterations in the conjunctival sac and lacrimal sac in chronic dacryocystitis - Jie Chen; Fangzheng Shi; Siya Chen; Yulu Liu; Yuxin Xu (Indian Journal of Ophthalmology)
Purpose: Dysbiosis of the microbial community in the lacrimal sac has been associated with the occurrence and development of chronic dacryocystitis. The aim of this study was to investigate the microbial characteristics of the conjunctival sac and lacrimal sac in patients with chronic dacryocystitis using 16S rRNA sequencing and explore their relevance to this condition. Methods: This was achieved through the application of Illumina MiSeq technology for the comprehensive sequencing of 16S rRNA genes in bacterial DNA samples isolated from the conjunctival and lacrimal sacs of 20 patients with chronic dacryocystitis. Results: The conjunctival sac microbiota showed slightly higher diversity compared to the lacrimal sac. However, their microbial communities were similar. In the cohort representing the lacrimal sac, there was a notable reduction in the relative abundance of Proteobacteria. Conversely, an increase in the relative richness of phyla such as Firmicutes, Actinobacteria, and Bacteroidetes was observed. Linear discriminant analysis and effect size analysis elucidated a significant enrichment of the Methylobacterium and Cetobacterium genera within the conjunctival sac cohort, in contrast to the lacrimal sac cohort. The dominant pathway in both sites was biosynthesis according to Kyoto Encyclopedia of Genes and Genomes analysis. Conclusion: In individuals suffering from chronic dacryocystitis, the microbiota of the lacrimal sac exhibits a reduced α-diversity and a comparable β-diversity, alongside exhibiting distinct taxonomic profiles when contrasted with the microbiota of the conjunctival sac.